Development of Electronic Parking Coupon Application in Bukit Gambir - Kan, Jia Qi; Abdullah, Noryusliza (Applied Information Technology And Computer Science, 2021)
Electronic parking coupon is proposed to replaced traditional parking coupon. This is because people need to buy the new coupon while visiting another area or region and find the store that selling parking coupon. Besides that, people in shopping mall or other places are difficult to top up their parking time because they need go back to the car. This project is focusing on drivers who are using the traditional coupon when parking in Bukit Gambir. The system is developed using Java language and it is based on Agile methodology. The development of this system is to help driver in Bukit Gambir to use E-parking Coupon Johor when they are in different area of Bukit Gambir.